Unregulated Workshop Practices and Consumer Protection: Addressing Unauthorized Fuel Siphoning - Ramadhan, Syahrul; Saputra, Arikha (Fakultas Hukum Universitas Islam Jakarta, 2025)
Unauthorized fuel siphoning by mechanics during motorcycle servicing raises significant concerns within the framework of consumer protection law. Such practices potentially infringe upon consumers’ rights to transparency, informed consent, and fair treatment, thereby questioning the scope of business accountability in service transactions. This study examines the underlying factors contributing to unauthorized fuel siphoning, analyzes the legal responsibilities of workshop operators, and evaluates available dispute resolution mechanisms. Employing an empirical juridical method, the research combines field interviews with consumers and workshop representatives and doctrinal analysis of Law No. 8 of 1999 on Consumer Protection and related regulations. The findings indicate that unauthorized fuel siphoning constitutes a breach of the duty of good faith and the obligation to provide accurate and transparent information, thereby giving rise to potential liability for damages. Cost-efficiency considerations in the servicing process were identified as a contributing factor to the practice. Disputes are generally resolved through non-litigation mechanisms, particularly negotiation. The study concludes that strengthening operational standards, enhancing service transparency, and reinforcing preventive and corrective consumer protection mechanisms are essential to ensuring effective legal protection in service-based commercial activities.